Modeling Potential Distribution of the Black-shanked Douc (Pygathrix nigripes) - Tuan Anh, Nguyen; Duc Minh, Le (VNU Journal of Science: Earth and Environmental Sciences, 2025)
The Black-shanked douc - Pygathrix nigripes (P. nigripes) is an endangered primate found only in a small region between Vietnam and Cambodia. In recent decades, the species populations have been significantly reduced in  their common strongholds because of the pressure from illegal hunting and habitat destruction. The actual distribution of this species remains poorly understood. To better understand the distribution patterns of this endangered primate, we collate localities from previous studies and our field surveys to model the douc’s potential distribution using MaxEnt, a widely used species distribution modeling method. The model results show that, the main distribution range of P. nigripes covers the region of Dak Lak, Khanh Hoa, Lam Dong, and Dong Nai provinces, with an area of approximately 62,000 km 2 . Based on the optimal model, we recommend future field surveys in several potential areas to identify unknown populations of the douc. We also suggest possible natural barriers of the Black-shanked douc and its relatives, and its implications for conservation activities.